Utilization of Technology In Developing Digital Marketing for MSMEs at Sate Taichan Geh Bang Nut in Bandar Lampung City - Selin Faradina; Febiola Efriani; Nelly Fitria; Vindi Millenia Putri; Rica Sherly Permatasari; Yuniarti Fihartini (Journal Of Community Service for Economics and Business, 2025)
The Industrial Revolution 4.0 era has encouraged MSMEs players to adopt digital marketing to reach the market. The purpose of the research is to optimize digital marketing in Sate Taichan Geh Bang Nut MSMEs in Bandar Lampung through the provision of Instagram-based social media-based marketing strategies. The method used is qualitative descriptive with observation, interviews, and documentation. The results show that the main challenges faced include suboptimal content design, engagement, and social media planning. To overcome this, the service program is designed with a debriefing on content design using Canva, creating a social media calendar, and effective hashtag strategies. The impact of this program has increased the number of Instagram account followers, the quality of interaction with the audience has increased, and the brand positioning is stronger. A planned digital marketing strategy is an important step to support the competitiveness of MSMEs in the digital era.